Ketahanan Varietas Padi terhadap Hama Penggerek Batang (Scirpophaga sp.) di Kampung Telaga Sari Kabupaten Merauke - Sembiring, Jefri; Wandikbo, Roni; Kusuma, Rangga; Mendes, Johana (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The rice stem borer (Scirpophaga sp.) is a significant pest of rice plants, causing substantial yield losses. This study aimed to assess the growth response of seven rice varieties to stem borer (Scirpophaga sp.) infestation. The research was conducted in Kampung Telaga Sari, Kurik District, Merauke Regency, from October 2022 to January 2023. The experiment followed a Randomized Complete Block Design (RCBD) with seven varieties and three replications per trial. The varieties tested were Inpari 32, Inpari 42, Cakrabuana, Siam-siam, CL 220, Sertani, and Mekongga. Each treatment was replicated three times, resulting in 21 experimental plots, each measuring 3 x 3 mÂ² with a planting distance of 20 x 20 cm, comprising 50 plants per plot. The research findings indicated significant differences in stem borer damage intensity at the 0.01 level of significance. The highest average attack intensity was observed in the Inpari 32 variety (5.44%), while the lowest average attack intensity was found in the Cakrabuana variety (2%).